2018
DOI: 10.3892/etm.2018.5842
|View full text |Cite
|
Sign up to set email alerts
|

N‑methyl pyrrolidone promotes ankle fracture healing by inhibiting inflammation via suppression of the mitogen‑activated protein kinase signaling pathway

Abstract: Abstract. N-methyl pyrrolidone (NMP), a small bioactive molecule, has the potential to stimulate bone formation and inhibit osteoclast differentiation. The aim of the present study was to investigate the effect of NMP on the inflammatory response and underlying molecular mechanisms in MG-63 cells. The mRNA and protein expression of cytokines from peripheral blood in children with or without ankle fracture were determined by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and ELISA, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Some studies have found through animal experiments that the expression of IL-1β protein in the joint cavity of mice is significantly reduced after blocking TNF-α, suggesting that TNF-α is related to the production of IL-1β protein [ 19 ]. Similar conclusions have been reached in cell experiments, where MSU crystals can more effectively promote the synthesis of IL-1β precursor and IL-18 in medium supplemented with TNF-α [ 20 ]. TNF-α also has dual effects on fracture: on the one hand, it reduces new bone formation, and on the other hand, it enhances bone resorption, improves OC activity, and reduces cortical bone quality.…”
Section: Discussionsupporting
confidence: 79%
“…Some studies have found through animal experiments that the expression of IL-1β protein in the joint cavity of mice is significantly reduced after blocking TNF-α, suggesting that TNF-α is related to the production of IL-1β protein [ 19 ]. Similar conclusions have been reached in cell experiments, where MSU crystals can more effectively promote the synthesis of IL-1β precursor and IL-18 in medium supplemented with TNF-α [ 20 ]. TNF-α also has dual effects on fracture: on the one hand, it reduces new bone formation, and on the other hand, it enhances bone resorption, improves OC activity, and reduces cortical bone quality.…”
Section: Discussionsupporting
confidence: 79%
“…Some studies have found through animal experiments that the expression of IL-1β protein in the joint cavity of mice is signi cantly reduced after blocking TNF-α, suggesting that TNF-α is related to the production of IL-1β protein [10] . Similar conclusions have been reached in cell experiments, where MSU crystals can more effectively promote the synthesis of IL-1β precursor and IL-18 in medium supplemented with TNF-α [11] . TNF-α also has dual effects on fracture: on the one hand, it reduces new bone formation, and on the other hand, it enhances bone resorption, improves OC activity, and reduces cortical bone quality.…”
Section: Typical Casessupporting
confidence: 82%
“…It contains bone-induced polypeptide biological factors, such as transforming growth factor -beta (TGF- beta), [ 14 ] which can promote the synthesis of type I collagen and osteoporosis. [ 14 ] They inhibit the inflammatory response, reduce the content of tumor necrosis factor-alpha (TNF-alpha) in serum, [ 15 ] and assist macrophage-derived cytokines to play a role in tissue repair. [ 16 ] According to the pathogenesis of RA in traditional Chinese and western medicine, UC-MSCs are pre-stimulated by the polypeptide of LG to promote the superposition of kidney-nourishing, bone strengthening, blood-activating, and collateral-opening, and also reduce the release of pro-inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%